Substrates, regulation, cellular functions, and disease associations of P4-ATPases - Hye-Won Shin; Hiroyuki Takatsu (Communications Biology)
Abstract P4-ATPases, a subfamily of the P-type ATPase superfamily, play a crucial role in translocating membrane lipids from the exoplasmic/luminal leaflet to the cytoplasmic leaflet. This process generates and regulates transbilayer lipid asymmetry. These enzymes are conserved across all eukaryotes, and the human genome encodes 14 distinct P4-ATPases. Initially identified as aminophospholipid translocases, P4-ATPases have since been found to translocate other phospholipids, including phosphatidylcholine, phosphatidylinositol, and even glycosphingolipids. Recent advances in structural analysis have significantly improved our understanding of the lipid transport machinery associated with P4-ATPases, as documented in recent reviews. In this review, we highlight the emerging evidence related to substrate diversity, the regulation of cellular localization, enzymatic activities, and their impact on organism homeostasis and diseases.